KEHILANGAN MATERIAL ENAMEL PADA PERMUKAAN BUKAL PREMOLAR SATU AKIBAT PERENDAMAN MINUMAN BERSODA (IN VITRO) - Dharma Novena Silaen (Fakultas Kedokteran Gigi Universitas Sumatera Utara, 2013)
Abstract Consuming soft drinks is a lifestyle in modern life, it is seen by the growing habit of consuming soft drinks that contains of acids with low pH (<5.5), especially among teenagers and children. Pepsi cola is one of the soft drinks (pH 2.6) which is currently widely consumed. Contacting of acidic soft drinks on tooth enamel causes demineralization. The purpose of this study was to evaluate the loss of material enamel surface on buccal premolar 1 due to soft drinks in woman aged 17 years. This study used experimental laboratory design that is Pretest and Postest Control Group Design. 5 premolars 1 in woman aged 17 years, every enamel surface is divided into two parts which half of buccal surface covered with wax and the other buccal surface was not covered with wax and then immersed in soft drinks (5 minutes) and saline (4 hours) with a repetition of 3 times daily for 6 consecutive days. Enamel surface was cut into 5x5x3mm on prominent buccal area and viewed used a Scanning Electron Microscope (SEM). Data was analyzed by using SPSS with chi-square. This study showed the loss of material enamel surface caused exposure by soft drinks. Analyzing by chi-square showed significant relation between soft drinks and loss of material enamel surface, surface roughness, enamel prisms, and enamel interprisms. The results indicated that there were clear boundaries between exposed and unexposed surfaces of soft drinks in the form of the surface height difference. Key words: Material of enamel surface, acid, soft drink